Evaluating the role of credit facilities as drivers to small scale rice farmers’ productivity in Wukari local government area, Taraba state, Nigeria - Ukpe, Udeme Henrietta; Saidu, Duwangs Moses (International Journal of Sustainable Agricultural Research, 2023)
The role played by credit for sustainable agricultural activities cannot be overemphasized. The study evaluated the role of credit facilities as drivers to small scale rice farmers’ productivity in Wukari Local Government Area Taraba State, Nigeria. A multi stage sampling procedure was used to sample 250 respondents from the study area. The study found that seed (p = 0.03), fertilizer (p = 0.01), and farm size (p = 0.01) were the key determinants of productivity for the rice farmers who had access to credit facilities while labour (p = 0.056) and seed (p = 0.01) were the determinants of productivity for the non-access to credit facilities counterparts. The finding show that years in school, farm size and age are the factors that influenced access to credit facilities. Finally, interest rate (92.8%), lack of collateral security (89.6%), lending criteria (72%) and government regulations (70.8%) are the major problem associated with access to credit facilities. It was therefore recommended that Public and private partnerships should be encouraged to develop innovative financial products and services tailored farmer’s activities with a goal of offering competitive interest rates. Continuous review and policies adaptation related to interest rates in agricultural lending to ensure they remain effective and responsive to changing economic conditions and the needs of farmers.